Characterizing Hypoglycemic Events during Saxagliptin Treatment in Type 2 Diabetes - Nichols, Emma Hitt (MD Conference Express, 2014)
Treatment of type 2 diabetes mellitus (T2DM) with saxagliptin increased the risk of major and minor hypoglycemic events, but it enabled more patients to reach an HbA1C target of less than 7% without hypoglycemia. This is according to a subanalysis of the Does Saxagliptin Reduce the Risk of Cardiovascular Events When Used Alone or Added to Other Diabetes Medications? study [SAVOR-TIMI 53; NCT01107886]. The main results of this multicenter, randomized, double-blind, placebo-controlled Phase 4 study have been published [Scirica BM et al. N Engl J Med 2013].